A solid-state lithium-oxygen battery operating at ambient temperature and full charge-discharge. (1st December 2022) - Zhu, De-Ming; Bai, Fan; Zhang, Yi-Nan; Yang, Ya-Nan; Sun, Zhuang; Deng, Jun-Wen; Zhang, Tao
Abstract: Solid-state Li-O2 batteries (SSLOBs) have been denoted as the holy grail in next-generation Li metal batteries for their high theoretical energy density, manipulation of ambient air to energy storage as well as high safety. However, the solid rigid interfaces both at the cathode and anode side introduce ultra-high resistances in the battery system and impede its operation under ambient temperature. Moreover, the high-reductive Li anode and semi-open cathode would cause severe side reactions during cycling which further degrade battery performance. To manage the above-mentioned issues, a rationally designed SSLOBs based on plastic crystal electrolyte is proposed in this study to enable SSLOBs operation at ambient temperature and in full charge-discharge mode. The brand-new Li-O2 battery has been improved mainly from two aspects. First, we propose a polyacrylonitrile (PAN) modified succinonitrile (SN) electrolyte (PAN-SN) to retard the polymerization of SN and meanwhile suppress the degradation of Li ionic conductivity. Second, we propose an alternative mixed electron/ion complex conductor (MEIC) cathode to coordinate with plastic crystal electrolyte with an expanded Li-O2 reactive zone and improved interfacial charge transfer during the charge-discharge process. The fabricated flexible SSLOBs based on PAN-SN electrolyte and MEIC cathode could be successfully fully charged-discharged (cutoff 2.0–4.5 V) for tens of cycles at ambient temperature under simulated air condition (20 vol% oxygen), with high-capacity retention of around 85 %. Graphical abstract: Unlabelled Image Highlights: A novel polyacrylonitrile-modified plastic crystal electrolyte for solid-state Li-O2 batteries was proposed. The undesirable polymerization of succinonitrile was suppressed by polyacrylonitrile modification. A mixed electron/ion complex conductor was proposed to construct continuous triple-phase boundaries. The cathode construction suppressed undesirable reactions between discharge product and succinonitrile.